THE IMPLEMENTATION OF THE SILENT WAY METHOD TO INCREASE STUDENTS’ ENGLISH VOCABULARY IN SMPN 3 SUKOHARJO - Saputri, Sukma Ajeng Damar; Sahid, Sahid (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
This study aimed to improve the vocabulary skills of 8th-grade students at SMP Negeri 3 Sukoharjo using the Silent Way method. The research adopted a Classroom Action Research (CAR) design, conducted over two cycles during the 2023/2024 academic year. The sample consisted of one randomly selected class from the 8th grade, and data were collected using a mixed-method approach, including interviews, observations, field notes, and tests. The pre-test and post-test scores were used to measure the effectiveness of the intervention. The study concluded that the Silent Way method effectively enhances vocabulary acquisition by engaging students and fostering active participation. These findings suggest that innovative, student-centered teaching methods can significantly improve language learning outcomes. Further research is recommended to explore the long-term effects of such methods on vocabulary retention and overall language proficiency.